Ethnic Research at the Sarawak Border : Exploring Diversity, Identity, and Cross-Border Relations - Dilah, Tuah (2024)
Abstract This presentation explores the rich ethnic diversity, identity, and cross-border relations along the Sarawak-Kalimantan border. The research highlights the shared cultural and linguistic heritage of indigenous communities, including the Selako, Iban, Bidayuh, Lun Bawang, and Kelabit peoples. Key areas of investigation include cultural and linguistic diversity, cross-border kinship ties, socioeconomic challenges, traditional ecological knowledge (TEK), and interethnic relations. The study employs ethnographic fieldwork, comparative analysis, and policy assessment to understand the complexities of ethnic identity, belonging, and the impact of colonial borders on community interactions. The findings aim to inform policymakers, preserve cultural heritage, and promote sustainable development in the region. Collaborative efforts with local communities and international partners, such as IAIN Pontianak, are emphasised to enhance the research's impact and support shared objectives. This research underscores the Sarawak-Kalimantan border as a unique cultural and linguistic melting pot, fostering greater understanding and harmony among diverse ethnic groups.